EARLY INTERVENTION POSSIBILITIES IN ASPECT OF INCLUSIVE EDUCATION - Prudņikova, Ilga; Jankovska, Jekaterīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Inclusive education is an essential component, which provides people with special needs state of society in the future. Nowadays   education, bringing together scientists, psychologists, educators theories and knowledge, gives off the focus early intervention idea. Early help is different sectoral expert professional advice and support. Fundamental of early intervention is inter-institutional cooperation that promote child development and socialization. Child's preparation to school is directly related to the timely, early assistance and support measures. Quality of inclusive education depends on all the parties of professional competence.